Assessment of Urban Rooftop Grid Connected Solar Potential in Nepal - Shrestha, Jagan Nath; Raut, Debendra Bahadur (Journal of the Institute of Engineering, 2020)
The power shortage problem faced by Nepal since last two decades is one of the major hurdles for its socio-economic development. At present load shedding is being managed by significant import of electricity from India thus increasing trade deficit of Nepal. The accelerated alternative methods of generation of electricity in Nepal need to be explored. This paper assesses the potential of rooftop solar Photovoltaic (PV) system in residential buildings in their major cities namely Kathmandu valley, Pokhara and Biratnagar of Nepal. The data indicated in this paper are collected from the predefined set of questionnaire and field survey in the randomly sampled households in 2016. Form the quantitative analysis of the data, it is found that the average roof top area available for PV installation in residential buildings are 14.5 sq.m, 12.45 sq.m and 19 sq.m for Kathmandu, Pokhara and Biratnagar cities respectively. Considering 557,027 residential buildings in Kathmandu; 77,523 in Pokhara and 33,075 in Biratnagar, total PV power potential is estimated to be 810 MWp, 96.5 MWp and 63.5 MWp in respective cities. To estimate the energy potential the annual average peaksun hours considered are 5.54, 5.58 and 5.13 for Kathmandu, Pokhara and Biratnagar city respectively, data taken from Solar and Wind Resource Assessment (SWERA) report. The total power potential in all three cities is found to be 970 MWp which could generate 1,310 GWh that comes out to be 24% of the electricity sold by Nepal Electricity Authority (NEA) in fiscal year 2017/18. If shade free roof top space available of the 50% residential buildings are utilized for PV installation (333,762 numbers), about 12% of the Nepal’s utility electricity sold in the fiscal year 2017/18 could be saved annually. The technical barriers for the grid connection of roof top solar is not a major issue now as NEA has set the guidelines for it.